(The Safety Control and Application of HACCP In packaged Drinking Water Industry) - Agus Sudibyo (Balai Besar Industri Agro, 2007)
The Indonesia market for bottled drinking water currently shows a very high rate of growth. Per capita consumption of packaged drinking water is about 32 liters per year and tend to be risen. The number of bottled drinking water registered in Indonesia are about 350 industries which produced as much 5 billions liters per year. Most of all drinking water production in Indonesia are produced by bottled drinking water industry. However, there are evidence, problem and fact that some of bottled drinking water was contained and it has not met the quality and safety standard. Since the nethods of contamination protection has been issued, the problem in bottled drinking water service establishment is to enforce which must include not only proper equipments nad installations but also training of the personel. The HACCP concept for preparation drinking water of bottled drinking water service has to be socialized with the simple language. Goevernment and inspection authorities should encourage the ready to drinking water industry managerial to apply the safety control and HACCP procedures to ensure safe drinking water production.